American government : - Landy, Marc (McGraw-Hill Higher Education, 2004)
This exciting, concise new text takes a unique political development approach to American government courses. Written by two pre-eminent scholars of American political development, Marc Landy and Sid Milkis, the text explores American government as an entity that evolves through the debates that have occurred in American politics and political culture over time. This approach gives readers a context for understanding the growth of U.S. systems and laws, and encourages critical thinking